KESEHATAN MENTAL DALAM PEMIKIRAN AL-GHAZALI DAN CLAUDE MASON STEELE - Muhammad Imdad; Muhammad Endy Fadlullah (LPPM Universitas Islam Ibrahimy Banyuwangi, 2025)
The issue of mental health is a hotly debated issue. Various events stemming from mental disorders are increasingly urgent to be taken seriously. Claude Mason Steele, an expert in social psychology, has a method to overcome threats that can disrupt human mentality, namely self-affirmation. The way self-affirmation works is by affirming to oneself positive values, even though they are not related to the threats received. Meanwhile, al-Ghazali has an introspective self-blame method, investigating the negative potential in oneself that is prone to causing mental disorders. This paper uses a comparative method that is presented by describing the thoughts of the two figures descriptively and then analysing and comparing them. The findings in this paper are several things. First, the difference in perspective between Claude Steele and al-Ghazali in reading mental health issues boils down to differences in their scientific perspectives, namely psychology and Sufism. Second, the views of al-Ghazali and Steele must be combined to produce a holistic reading of mental health issues and their handling.